Dialium heterophyllum (Fabaceae: Dialioideae), a new tree species from the Amazon - Falcão, Marcus José De Azevedo; Mansano, Vidal De Freitas (Phytotaxa, 2020)
In this work, we describe Dialium heterophyllum, a new species for the largest genus in the diverse and morphologically unique legume subfamily Dialioideae. Dialium, with 32 species, has its highest diversity in tropical Africa and Asia, with four species accepted until now in the Neotropics. The fifth species described here reinforces the idea that a large portion of the Neotropical diversity, notably in the Amazon, is still unknown. Dialium heterophyllum is restricted to the south of the Amazon Basin in Brazil and Bolivia, areas under intense anthropic pressure in recent years. Due to its floral morphology, the species appears to be closely related to the other Neotropical species of the genus, differing by its reduced leaf rachis with unifoliolate to trifoliolate leaves, generally opposed to sub-opposed leaflets, the terminal leaflet much longer than the lateral ones (when present) and than the leaf rachis. We provide illustrations, distribution maps, a conservation risk assessment and an identification key.